2015
DOI: 10.1111/2041-210x.12417
|View full text |Cite
|
Sign up to set email alerts
|

A new method to analyse species abundances in space using generalized dimensions

Abstract: Summary Species–area relationships (SAR) and species‐abundance distributions (SAD) are among the most studied patterns in ecology, due to their application to both theoretical and conservation issues. One problem with these general patterns is that different theories can generate the same predictions, and for this reason, they cannot be used to detect different mechanisms of community assembly. A solution is to search for more sensitive patterns, for example by extending the SAR to the whole SAD. A generaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…It has been assumed that the features of fractal structures are present in the patterns of community ecology (Saravia, 2015;Våge and Thingstad, 2015). Cases of power law dependency have been detected in rank-abundance distributions of microbial communities (Feranchuk et al, 2018a), as it is shown in Fig.…”
Section: Detection Of Power-law Distributions Inmentioning
confidence: 99%
“…It has been assumed that the features of fractal structures are present in the patterns of community ecology (Saravia, 2015;Våge and Thingstad, 2015). Cases of power law dependency have been detected in rank-abundance distributions of microbial communities (Feranchuk et al, 2018a), as it is shown in Fig.…”
Section: Detection Of Power-law Distributions Inmentioning
confidence: 99%
“…It was demonstrated that neutral and niche mechanisms could produce the same RAD (Volkov et al , Chisholm and Pacala ), so it might not be useful for determining the proximity to the critical point. We found that there is a change in the RAD when the critical point is approached but these changes are small and will probably go undetected (Saravia ). The shape of the RAD is highly dependent on the metacommunity, which is difficult to estimate as a baseline, and thus there is no RAD characteristic of a community near the critical point.…”
Section: Discussionmentioning
confidence: 77%
“…Our criteria to stop enlarging the scale is that the species abundance distribution (SAD) of the discretized lattice should not be statistically different from the original SAD. To test this we use the Anderson‐Darling statistic with a randomization procedure using the R package kSamples (Scholz and Zhu ); this statistic has proven powerful to detect different kinds of communities using SAD (Saravia ). With this procedure we obtained a scale of 1 m, and thus used a lattice of 1000 × 500 sites.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we study the phase transition between neutral and niche dynamics from a spatial point of view by applying methods of percolation theory. We will use a spatially explicit neutral model where niche dynamics is represented as a competitive hierarchy (Saravia 2015). Our first objective is to demonstrate the existence of the phase transition in our spatial neutral-niche model triggered by competition intensity; we show that the phase transition is determined by the geometric characteristics of the species patches, and that the niche state that emerges after the critical point has lower species diversity and richness.…”
Section: Introductionmentioning
confidence: 99%